Environmental activities of a petrochemical company as a sustainable factor of the city and region. Issue 1 (July 2020) - Mironova, Margarita; Romanova, Anna; Evgeniya, Irina; Galeeva, Irina; Egorov, Danila; Akhmetova, Alena
Abstract: The paramount objective of modern society is to preserve a livable environment for generations to come. In addition to the need to restore the impaired qualities of the environment, measures also must be taken to preclude environmental disasters from happening both now and in the future. The formation of a balanced regional system of cities is hampered by the deterioration of the environmental situation and a decrease in environmental quality indicators. The concentration of industrial sites and vehicles represents one of the biggest adverse anthropogenic factors which stems from the human impact on the environment. Growing industrial clusters and the rising number of vehicles in large cities result in a critical environmental situation. Environmental monitoring measures, once introduced, will facilitate the sustainable development of urban areas and the economy of the region.